Patient perspectives on the implementation of routinised syphilis screening with HIV viral load testing: Qualitative process evaluation of the Enhanced Syphilis Screening Among HIV-positive Men trial - Kinnon R MacKinnon; Ramandip Grewal; Darrell HS Tan; Rodney Rousseau; John Maxwell; Sharon Walmsley; Paul A MacPherson; Anita Rachlis; Nisha Andany; Sharmistha Mishra; Vanessa G Allen; Ann N. Burchell (BMC, 2021)
Abstract Background Syphilis infections have been on the rise, affecting men living with HIV in urban centres disproportionately. Since individuals in HIV care undergo routine blood testing, HIV clinics provide practical opportunities to conduct regular and frequent syphilis testing. Following the implementation of a routine syphilis testing intervention in HIV outpatient clinics, we conducted a qualitative process evaluation of patient experiences to measure patient acceptability, barriers to implementation, and facilitators of successful uptake. Methods Upon completion of the trial, which took place at four HIV outpatient clinics in Toronto and Ottawa, Canada, we recruited male patients attending these clinics from November 2017 to April 2018. Interviews were conducted on-site and were audio-recorded and transcribed verbatim. All participants provided written informed consent. Interview data were analyzed using grounded theory, assessing qualitative modulators of effective uptake of routinised syphilis testing. Results A total of 21 male patients were interviewed. Overall, interviewees found the clinical intervention acceptable, endorsing the practice of routinising syphilis testing alongside regular viral load bloodwork. Some men preferred, based on their self-assessment of syphilis risk, to opt out of testing; we considered this as a potential barrier to uptake of population-wide routinised syphilis testing. Interviewees also identified multiple facilitators of successful uptake, including the de-stigmatising of STI testing as a consequence of the universal nature of routinised testing. Participants recommended a routinised syphilis screening intervention to give patients peace of mind surrounding their sexual health. Participants identified HIV care clinics as comfortable and efficient locations to offer testing. Conclusions Overall, most men were in support of implementing routinised syphilis testing as part of standard HIV care. From the patient perspective, HIV care clinics are convenient places to be tested for syphilis, and the routine approach was viewed to have a de-stigmatisng effect on syphilis testing. Trial registration ClinicalTrials.gov NCT02019043; registered December 23, 2013.